2018
DOI: 10.1111/1750-3841.14205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro Human Digestion on the Antioxidant Activity and Stability of Lycopene and Phenolic Compounds in Pork Patties Containing Dried Tomato Prepared at Different Temperatures

Abstract: In this study, we revealed that in vitro human digestion increases the antioxidant activities of tomato powder. In addition, tomato powder dried at the highest temperature (100 °C) showed the highest antioxidant activity. Therefore, tomato powder at 100 °C could be used as strong antioxidants in meat products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…In addition, the remaining antioxidants bound to insoluble fraction reached the colon and were probably released by enzymatic digestion. In a similar with the present study, Kim and Hur (2018) also reported that the intestinal digestion caused a 5-fold increase in TAC of pork patties and its activity remained stable through the colon.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the remaining antioxidants bound to insoluble fraction reached the colon and were probably released by enzymatic digestion. In a similar with the present study, Kim and Hur (2018) also reported that the intestinal digestion caused a 5-fold increase in TAC of pork patties and its activity remained stable through the colon.…”
Section: Resultssupporting
confidence: 92%
“…However, it is present along with other carotenoids and bioactive compounds in a balanced diet, and their synergistic effects have not been investigated extensively (Shi, Qu, Kakuda, Yeung, & Jiang, 2004). The combination of lycopene and tocopherol suppressed the growth of mammary tumors in rats (Al‐Malki, Moselhy, & Refai, 2012), and that of lycopene and phenolic compounds increased the antioxidant activity during the simulated digestion process in vitro (Kim & Hur, 2018). Epidemiological studies have shown that tomato extract rich in lycopene and other carotenoids prevented cardiovascular disease by inhibiting platelet activation (O'Kennedy et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…After digestion, the polyphenol content showed a ten-fold increase in most of the analyzed burgers (Fig. 1A, grey bars) due to the further solubilization of polyphenols in digestive fluids (Kim & Hur, 2018;Pešić et al, 2019). Digestive enzymes are able to transform phenolic compounds into different structural forms possessing alterated chemical properties.…”
Section: Polyphenol Contents and Antioxidant Profiles Of Cooked Beef ...mentioning
confidence: 95%
“…Moreover, the change of pH from an acidic to the alkaline environment, during intestinal digestion, may improve the antioxidant capacity of phenolics through the deprotonation of the hydroxyl moieties present on their aromatic ring (Kim & Hur, 2018). Nevertheless, the polyphenol pattern of digested burgers (Fig.…”
Section: Polyphenol Contents and Antioxidant Profiles Of Cooked Beef ...mentioning
confidence: 99%